Pengaruh Metode Demonstrasi dan Modifikasi Alat Terhadap Hasil Belajar Servis Atas Permainan Bola Voli Ditinjau dari Motivasi Belajar Peserta Didik - Supono, Supono (Universitas Nusantara PGRI Kediri, 2023)
This study was designed for the following purposes: (1) To find out whether there are differences in the effect of the Demonstration Method and modification of the tool on learning outcomes of the upper serve in the volleyball game of class VII boys at SMPN 1 Karangrejo and SMPN 2 Karangrejo Tulungagung. (2) To find out whether there are differences in the learning outcomes of serving in the volleyball game of class VII boys at SMPN 1 Karangrejo and SMPN 2 Karangrejo Tulungagung who have high learning motivation and low learning motivation. (3) Knowing whether there is an interaction effect between the demonstration method and modification of tools as well as high or low learning motivation on the learning outcomes of the upper serve in the volleyball game of class VII male students at SMPN 1 Karangrejo and SMPN 2 Karangrejo. To obtain data, the author uses two types of instruments, namely the service skill test and the learning motivation questionnaire. The population and sample that the writer uses are male students of class VII SMPN 1 Karangrejo and SMPN 2 Karangrejo who will be analyzed using two-way ANOVA statistics. From the research data, the following results were obtained: Of the 80 students who were given the demonstration method, there were 40 students with high motivation and 40 students with low motivation. Likewise for those who were given the tool modification method, as well as for their learning motivation, 40 students had high motivation and 40 students had low motivation. Based on the analysis of the effect of the demonstration method and modification of the tool on the learning outcomes of the upper service, it is obtained that F count is 161,307 and 85,983 > F table = 3,967, and the difference in learning outcomes of students who are highly motivated and low is obtained F count of 27,879 and 50,809> F table = 3,967 . While the results of the analysis of the interaction between the demonstration method and modification of tools as well as high or low learning motivation on service learning outcomes obtained F count of 3.442 and 0.004 < F table = 3.967, the following conclusions are obtained: (1) There is a difference in the effect of the demonstration method and modification of the tool on the results of learning the upper serve in the volleyball game of class VII male students at SMPN 1 Karangrejo and SMPN 2 Karangrejo Tulungagung. The effect of giving the tool modification method is better than the demonstration method. (2) There are differences in the learning outcomes of serving in the volleyball game of class VII male students at SMPN 1 Karangrejo and SMPN 2 Karangrejo Tulungagung who have high learning motivation and low learning motivation. Students with high motivation have better scores than students with low motivation. (3) There is no interaction effect between the demonstration method and tool modification as well as high or low learning motivation on the learning outcomes of the upper serve in the volleyball game of class VII male students at SMPN 1 Karangrejo and SMPN 2 Karangrejo.